2019
DOI: 10.3390/coatings9030156
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Doped Hydroxyapatite Thin Films Prepared by Sol–Gel Spin Coating Procedure

Abstract: In this study, ZnHAp layers deposited on a Si substrate were obtained by a sol–gel spin-coating procedure. The ZnHAp solutions used to obtain the ZnHAp coatings were investigated by dynamic light scattering (DLS) analysis, ζ-potential, ultrasound measurements, and flame atomic absorption spectrometry (AAS). The average measured hydrodynamic diameter from the DLS analysis, ζ-potential, and ultrasound measurements were analyzed so as to characterize and estimate the stability of the ZnHAp nanoparticles. The AAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 55 publications
6
18
0
Order By: Relevance
“…The maximum inhibitory concentration of Zn 2%-HA to Gram-positive bacteria and Gram-negative bacteria was 50 ± 5% and 77 ± 5%, respectively [44]. The antimicrobial effect of Zn-HA layer on the growth of candida albicans showed that even after 8 h of incubation, the growth of fungal cells was inhibited and weakened with time [45]. Therefore, the use of Zn-HA in bone tissue engineering scaffolds has the effect of antibacterial and regulating immune cells, which can increase the value of scaffold materials.…”
Section: Zinc Doped Hydroxyapatite (Zn-ha)mentioning
confidence: 97%
“…The maximum inhibitory concentration of Zn 2%-HA to Gram-positive bacteria and Gram-negative bacteria was 50 ± 5% and 77 ± 5%, respectively [44]. The antimicrobial effect of Zn-HA layer on the growth of candida albicans showed that even after 8 h of incubation, the growth of fungal cells was inhibited and weakened with time [45]. Therefore, the use of Zn-HA in bone tissue engineering scaffolds has the effect of antibacterial and regulating immune cells, which can increase the value of scaffold materials.…”
Section: Zinc Doped Hydroxyapatite (Zn-ha)mentioning
confidence: 97%
“…The quantitative assays of the antifungal activity of both 5SmHAp suspensions and coatings were done using an adapted method (E2149-10; ASTM International) [30,31], as previously described [32]. The experiments were performed in triplicate and the results of the results were expressed as mean ± SD.…”
Section: In Vitro Antifungal Activitymentioning
confidence: 99%
“…The antifungal activity of HApAg5 and HApAg20 suspensions and thin layers was also evaluated by a quantitative assay. The quantitative assays of the antifungal properties of HApAg5 and HApAg20 suspensions and thin layers after 24 and 48 h was performed using an adapted method (E2149-10; ASTM International) [29,30] previously described in Predoi et al [31]. The experiments were done in triplicate and the results were presented as mean ±SD.…”
Section: In Vitro Antifungal Assaysmentioning
confidence: 99%